SPECTRAL PROPERTIES AND GEOLOGIC PROCESSES ON EROS FROM COMBINED NEAR NIS AND MSI DATA SETS - Izenberg N.R.; Murchie S.L.; Bell III J.F.; McFadden L.A.; Wellnitz D.D.; Clark B.E.; Gaffey M.J. (My University, 2003)
From April 24 to May 14, 2000, the Near Earth Asteroid Rendezvous (NEAR) Shoemaker mission's near infrared spectrometer (NIS) obtained its highest resolution data of 433 Eros. High signal-to-noise ratio NIS reflectance spectra cover a wavelength range of 800–2400 nm, with footprint sizes from 213 times 427 m to 394 times 788 m. This paper describes improvement in instrument calibration by remediation of internally scattered light; derivation of a “pseudo channel” for NIS at 754 nm using Multispectral Imager (MSI) Eros approach maps at 951 and 754 nm; synthesis of a 3127-spectrum high-resolution data set with the improved calibration and expanded wavelength coverage; and investigation of global and localized spectral variation with respect to mineralogy, composition, and space weathering of Eros, comparing the findings with previous analyses. Scattered light removal reduces the “red” slope of Eros spectra, though not to the level seen by telescopic observations. The pseudo channel completes sampling of Eros' 1 micron (Band I) absorption feature, enabling direct comparison of NIS data with other asteroid and meteorite spectra without additional scaling or correction. Following scattered light removal and wavelength range extension, the spectral parameters of average Eros plot well inside the S(IV) field of Gaffey et al. (1993) and are consistent with the L6 chondrite meteorite fields of Gaffey and Gilbert (1998). Although Eros shows no evidence of mineralogical heterogeneity, modest spectral variations correlate with morphologically and geographically distinct areas of the asteroid. Eros bright-to-dark spectral ratios are largely consistent with laboratory “space weathering” experiment results and modeling of space weathering effects. Eros brightness variation unaccompanied by significant spectral variation departs from “lunar-type”—where band depths, slopes, and albedoes all correlate—and “Ida-type”—where significant spectral variation is unaccompanied by corresponding brightness variation. The brightest areas on Eros—steep crater walls—have lesser spectral slope and deeper Band I, consistent with exposure of “fresher,” less space weathered materials. Bright crater slope materials have opx/(opx + olv) of 0.24–0.29 and may be more representative of the subsurface mineralogy than “average” Eros, which is probably affected by space weathering. The floors of the large craters Psyche and Himeros have lower albedo and contain the most degraded or altered looking materials. NIS spectra retain a “red” spectral slope at greater than 2 microns. The recalibrated and expanded NIS spectra show better agreements with mixing models based on space weathering of chondritic mixtures.